(untitled) (The Research of Medical Science Review, 2025)
Background: The incidence of postoperative complications following abdominal hysterectomy remains a significant concern in gynecological surgery. Metabolic syndrome (MetS), a cluster of cardiovascular and metabolic risk factors, may predispose patients to adverse surgical outcomes due to its systemic effects on inflammation, immunity, and healing. Objectives: To determine the association between metabolic syndrome and the frequency of postoperative surgical complications in patients undergoing abdominal hysterectomy. Study Design & Setting: A prospective observational study conducted at the Shalamar Medical & Dental College, Lahore over a period of six months. Methodology: A total of 120 women aged 35–65 years undergoing elective abdominal hysterectomy for benign conditions were enrolled. Metabolic syndrome was diagnosed using NCEP ATP III criteria. Postoperative complications, including wound infection, dehiscence, febrile morbidity, urinary tract infection, thromboembolism, and prolonged hospital stay (>5 days), were recorded up to 30 days postoperatively. Data were analyzed using SPSS version 25.0; chi-square test was applied with p ≤ 0.05 considered statistically significant. Results: Metabolic syndrome was present in 66 (55%) patients. Postoperative complications occurred in 59.1% of patients with MetS compared to 24.1% without (p < 0.001). Wound infection (24.2% vs. 9.3%), febrile morbidity (19.7% vs. 9.3%), and prolonged hospital stay (33.3% vs. 11.1%) were more frequent among the MetS group. All thromboembolic events occurred in MetS patients. Conclusion: Metabolic syndrome is significantly associated with increased postoperative complications following abdominal hysterectomy. Preoperative identification and management of MetS may help reduce surgical morbidity.